Determinants of Self-Employment in Finland - Dürr, Alvar (2025)
This thesis studies how self-employment is impacted by different variables in Finland. The variables included are gender, age, education, numeracy, literacy and problem-solving skills in technology-rich environments. The variables are first examined through prior research results and theoretical views. Using data from the OECD’s Programme for the International Assessment of Adult Competencies (PIAAC), logistic regression models are employed to estimate the likelihood of selfemployment.